Patient analysis and case-control investigation for high-output ileostomy control with glucagon (PACIFHIC-G) like peptide-1 analogues: a case control study - Castro-Segovia, Agustín; Ramirez-Garcia , Jorge Arturo (International Journal of Research in Medical Sciences, 2023)
Background: High ostomy losses (HOL) in the early postoperative (PO) period after an ileal resection are in an adaptation phase. After resection of the terminal ileum or proximal colon L cells are lost, this reduces the synthesis of glucagon-like peptide (GLP), its loss accelerates intestinal transit and gastric acid hypersecretion. An adequate adaptation phase is induced by enterotrophic hormones such as GLP. In this case control study, we performed an analysis of clinical outcomes with a conventional treatment compared with liraglutide intervention, a GLP-1 analogue. Methods: A single center, case-control study, from January 2021 to April 2023, patients had an ileal resection >20 cm, >18 years old, previously treated with loperamide 12 mg and omeprazole 80 mg, continued >1500 ml output at 48 hours PO, 30 patients where collected, 15 patients followed with a watch and wait approach and 15 patients treated 0.6 mcg of liraglutide every day for 8 weeks. Results: Clinical outcomes were followed for 6 months. Centimeters of resection had a statistically significant difference p<0.001 (control 20-180 cm vs. liraglutide 20-330 cm). Clinical outcomes with a significant difference where hospital length stay p<0.01 (control 4-133 days vs. 1-51 days) and hypovolemic shock p<0.05 (control 5 patients vs. 0 patients). Kaplan-Meier curve an 80% vs 100% 30 day survival rate in controls and liraglutide respectively. Conclusions: This is the first study with patients with HOL using liraglutide as an adaptation therapy. Patients had better clinical outcomes in mortality, length stay and hypovolemic shock.